A Phenomenological Inquiry into the Meaning Ascribed to Physical Activity by Brazilian Men with Visual Impairments. (September 2018) - Haegele, Justin A.; Hodge, Samuel R.; Filho, Paulo Gutierres; Ribeiro, Nillianne; Martínez-Rivera, Christian
Introduction: Research examining how adults with visual impairments experience physical activities is currently limited to specific age ranges (for example, youths or older adults) and geographic locations (such as Europe and North America). In an effort to extend the current literature base, the study presented here focuses on a cohort of young or middle-aged adults with visual impairments who live in Brazil. Thus, the purpose of this exploratory study was to examine the meaning Brazilian adults with visual impairments ascribed to their physical activity experiences. Methods: This study was situated in the qualitative paradigm utilizing a phenomenological design. Three male participants (aged 22 to 47 years) were purposively recruited to participate. The main source of data for this study was a focus group interview using an open-ended, guided approach that was recorded on audiotape. A three-step, line-by-line, thematic analysis, informed by the phenomenological research approach, was utilized to extract meaning from the participants' experiences. Several strategies were employed to reduce subjective bias, establish trustworthiness, and enhance transferability. Results: Two interrelated themes emerged when participants described how they experienced physical activities and the meaning they ascribed to those experiences. The first theme, physical activity–indispensable, describes the importance the participants ascribed to physical activity engagement and the benefits that they garnered from these experiences. The second theme, perceived physical activity impediments, exposed the obstacles participants experienced when trying to engage in physical activities. Discussion: This study's findings expose the meaning that a cohort of Brazilians with visual impairments ascribe to physical activity engagement. The participants explained how engagement in physical activity helped alleviate some social issues they previously experienced, but also noted barriers to engaging in these activities. Implications for practitioners: Programs targeting physical activity promotion for adults with visual impairments should show the reported benefits of engaging in physical activity programs while attempting to manage potential obstacles that would discourage a physically active lifestyle.